Statistical Analysis of Properties of Compact Yarn Produced from Different Process - Siddiqua, Toufiqua; Reza, Md. Alimur; Altaf, Habiba (European Scientific Journal, ESJ, 2019)
Compact spinning system is a great modification of ring spinning system. It brings a revolution over ring spinning system in case of hairiness and strength of yarn. In this paper, three yarn of “34’s Ne” count was produced in three different spinning systems termed as conventional Ring, Suessen Elite compact, and RoCoS (Rotorcraft) compact spinning system. During processing, all the processing parameters and the environment were kept the same in the case of the compact spinning system. Yarn properties are then tested with Uster Evenness Tester 6 and Mesdan strength tester. Statistical analysis like t-test paired two samples for means for all the properties of two compact yarns such as unevenness percentage, imperfection index, hairiness, tenacity, elongation, and count strength product were performed using Microsoft Excel 2013. Suessen Elite compact spinning system shows good results than another compact spinning system. It was found from the statistical analysis that there is no significant difference in the maximum properties of two compact spinning systems, especially in hairiness and tenacity, as these two properties are crucial in the compact spinning system.